1986
DOI: 10.1159/000124444
|View full text |Cite
|
Sign up to set email alerts
|

Estrous Cycle Variations in Cholecystokinin and Substance P Concentrations in Discrete Areas of the Rat Brain

Abstract: Cholecystokinin (CCK) and substance P (SP) were measured in discrete areas of the rat brain at different stages of the estrous cycle. Significantly higher levels of CCK were found in the lateral septum during diestrus as compared to proestrus. In the parietal cortex, CCK concentrations were significantly higher in diestrus than in proestrus. In the amygdala, estrous levels of CCK were significantly higher than proestrous levels. SP concentrations were significantly higher in diestrus than in proestrus in the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
1

Year Published

1987
1987
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 15 publications
0
36
1
Order By: Relevance
“…It is well documented that SP and/or related tachykinins are sexually dimorphic (Frankfurt et al, 1985;McKay, 1987, 1989), show estrous cycle variations (Frankfurt et al, 1986), and undergo changes in staining following hormonal treatment (Blaustein et al, 1991;Swann and Newman, 1992;Akesson, 1994). Brain areas that show SPl-ir include the anterior pituitary, ventromedial nucleus of the hypothalamus, medial nucleus of the amygdala, bed nucleus of the stria terminalis, and the medial preoptic area, all of which mediate steroidal induction of reproductive Increased SPLir input to the PPn-VT is correlated with androgen-induced chirping behavior in females.…”
Section: Androgen-induced Changes In Spi-irmentioning
confidence: 99%
“…It is well documented that SP and/or related tachykinins are sexually dimorphic (Frankfurt et al, 1985;McKay, 1987, 1989), show estrous cycle variations (Frankfurt et al, 1986), and undergo changes in staining following hormonal treatment (Blaustein et al, 1991;Swann and Newman, 1992;Akesson, 1994). Brain areas that show SPl-ir include the anterior pituitary, ventromedial nucleus of the hypothalamus, medial nucleus of the amygdala, bed nucleus of the stria terminalis, and the medial preoptic area, all of which mediate steroidal induction of reproductive Increased SPLir input to the PPn-VT is correlated with androgen-induced chirping behavior in females.…”
Section: Androgen-induced Changes In Spi-irmentioning
confidence: 99%
“…The neuroactive peptide cholecystokinin (CCK) has also been implicated in the control of reproductive behavior (21)(22)(23), and CCK levels in specific parts of the forebrain are sensitive to alterations in levels of circulating gonadal steroids (24,25). In addition, a sexual dimorphism in the number of CCK-immunoreactive cells within the medial preoptic nucleus has recently been found (26 Neurobiology: Simerly and Swanson was completely blocked when immunohistofluorescence staining was attempted with serum that had been preincubated with an excess (0.5 mg/ml) of synthetic CCK and then diluted to the working dilution.…”
mentioning
confidence: 99%
“…Thus, in an early report by Frankfurt and co-workers (Frankfurt et al, 1986), CCK-LI concentration was found to be reduced during pro-estrous in the amygdala when levels of estrogen are high. A trend towards a decrease in CCK-LI was also observed in the hippocampus in the same study, but did not reach significance.…”
Section: Discussionmentioning
confidence: 86%
“…CCK fluctuates during the estrous cycle in several brain regions (Frankfurt et al , 1986, Hilke et al , 2007 and the concentration of CCK-like immunoreactivity (LI) was found to be lowest during the pro-estrous phase, when the concentration of estrogen in plasma was at its highest level. Limited studies have shown that both CCK and its receptors are sensitive to estrogen (Micevych et al , 1996, Micevych et al , 1997.…”
Section: Introductionmentioning
confidence: 99%